1998
DOI: 10.1073/pnas.95.19.11083
|View full text |Cite
|
Sign up to set email alerts
|

Δ5-Androstenediol is a natural hormone with androgenic activity in human prostate cancer cells

Abstract: It is known that androst-5-ene-3␤,17␤-diol (Adiol), a precursor of testosterone (T), can activate estrogen target genes. The androgenic activity of Adiol itself, however, is poorly understood. Using a transient transfection assay, we here demonstrate in human prostate cancer cells that Adiol can activate androgen receptor (AR) target genes in the presence of AR, and that AR coactivator ARA70 can further enhance this Adiol-induced AR transcriptional activity. In contrast to this finding, an active metabolite of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
115
1
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 141 publications
(124 citation statements)
references
References 22 publications
(19 reference statements)
6
115
1
2
Order By: Relevance
“…Recently, we demonstrated that another adrenal androgen and precursor of T, D 5 -androstenediol, possesses intrinsic androgenic activity and that both of the antiandrogens fail to block D 5 -androstenediol-induced AR transcriptional activity in prostate cancer cell lines. 12 Although, in the present study, it is possible that D 4 -dione could convert into T in PC-3 or LNCaP cells and thereby induce CAT activity, the blockage of D 4 -dione action might improve androgen ablation therapy. Furthermore, these results will enhance our understanding and may lead to changes in the treatment of prostate cancer. )…”
mentioning
confidence: 60%
“…Recently, we demonstrated that another adrenal androgen and precursor of T, D 5 -androstenediol, possesses intrinsic androgenic activity and that both of the antiandrogens fail to block D 5 -androstenediol-induced AR transcriptional activity in prostate cancer cell lines. 12 Although, in the present study, it is possible that D 4 -dione could convert into T in PC-3 or LNCaP cells and thereby induce CAT activity, the blockage of D 4 -dione action might improve androgen ablation therapy. Furthermore, these results will enhance our understanding and may lead to changes in the treatment of prostate cancer. )…”
mentioning
confidence: 60%
“…9 We then found that ADEK has anti-Adiol effect on AR transcription in prostate cancer cells. 16 In our study, we also measured MMTV-Luc activity to determine whether HAD and OAK inhibit Adiol-induced AR transcription.…”
Section: Anti-adiol Effect Of Steroid Derivatives On Ar Transcriptionmentioning
confidence: 84%
“…6,9,11,16,17 PSA-Luc containing a natural 6.0 kb promoter and a synthetic (ARE)4-Luc containing 4 copies of androgen response element (ARE) were kindly provided by Dr. A. Mizokami (Kanazawa University, Kanazawa, Japan) and Dr. M.L. Lu (Harvard Medical School, Boston, MA), respectively.…”
Section: Chemicals and Plasmidsmentioning
confidence: 99%
See 2 more Smart Citations